(untitled) (Quinto Sol, 2024)
During the last military dictatorship that ruled Argentina (1976-1983), the mayor of the city of Buenos Aires, Osvaldo Cacciatore, projected an ambitious urban policy aimed at showing a clean and orderly city, connected to the values of high culture. In this last sense, a great work was projected: the Centro Cultural Ciudad de Buenos Aires (CCCBA). In 1979, the municipality ordered the transfer of a building in the Recoleta neighborhood to the National Secretary of Culture. The idea was to build a large cultural center like the Pompidou Center in Paris, under the direction of architects Clorindo Testa, Luis Benedit and Jaques Bedel. In 1980 the first part of the project was inaugurated, which was projected to be larger and ready in its entirety in 1982. In this paper we analyze the origin of the CCCBA project, the dimension of the work that was planned and the one that finally took shape, the references that the designers had in mind and the uses that were intended to be given to this space. In a second moment, we inquired into the different managements of the center and the artistic actions that took place between 1981 and 1983 and we analyzed which cultural actors and artists were part of this cultural space.